Online Pharmaceutical Management System - Ernest E, Onuiri; Inalegwu G, Oyebanji; Solomon A, Fayehun; Sam-David, Chukwujioke (European Scientific Journal, ESJ, 2016)
Pharmaceutical practices have evolved over time to become fully encompassed in all aspects of pharmacy itself. Such practices include: dispensing of drugs, consultation, drug regulation, and the sale of these drugs. The community pharmacies and hospital pharmacies have key roles to play in the pharmaceutical practices. For the community pharmacies in Sub- Saharan Africa, a strict approach to the sale and dispensation of drugs is not normally the case, due to the fact that laws governing pharmaceutical practices have not been fully enforced. On the part of the hospital pharmacies, there is a more controlled approach to the dispensing of drugs, as the prescriptions are readily available from the in-house doctors. There is a need for these practices to be fully enforced, and a management system introduced to the fray. With software such as the Online Pharmaceutical Management System, which provides a platform has been provided to help with drug regulation, as well as providing ease to all parties involved. The methodology used in the implementation of the software is the Incremental Model of System Development Life Cycle, which allows room for scalability as time goes on. Creating an Online Pharmaceutical Management System would help in pharmaceutical practices for all parties involved. It is eminent that the system provides a safe, secure and verified platform for all parties which help to bridge the communication gap and provide legitimate drugs. Therefore, if all recommendations are strictly adhered to, there will be strict monitoring and regulation of how drugs are circulated and a decrease in the spread of fake drugs.